Ovarian Vein Thrombosis: A Narrative Review - Riva, Nicoletta; Calleja-Agius, Jean (Hämostaseologie, 2020)
Ovarian vein thrombosis (OVT) is a rare type of venous thromboembolism. The most common risk factors for OVT include pregnancy, oral contraceptives, malignancies, recent surgery, and pelvic infections; however, in 4 to 16% of cases, it can be classified as idiopathic. Most of the available information regards pregnancy-related OVT, which has been reported to complicate 0.01 to 0.18% of pregnancies and to peak around 2 to 6 days after delivery or miscarriage/abortion. The right ovarian vein is more frequently involved (70–80% of cases). Clinical features of OVT include abdominal pain and tenderness, fever, and gastrointestinal symptoms. The most typical finding is the presence of a palpable abdominal mass, although reported in only 46% of cases. OVT can be the cause of puerperal fever in approximately a third of women. Ultrasound Doppler is the first-line imaging, because of its safety, low cost, and wide availability. However, the ovarian veins are difficult to visualize in the presence of bowel meteorism or obesity. Thus, computed tomography or magnetic resonance imaging is often required to confirm the presence and extension of the thrombosis. In oncological patients, OVT is often an incidental finding at abdominal imaging. Mortality related to OVT is nowadays low due to the combination treatment of parenteral broad-spectrum antibiotics (until at least 48 hours after fever resolution) and anticoagulation (low-molecular-weight heparin, vitamin K antagonists, or direct oral anticoagulants). Anticoagulant treatment duration of 3 to 6 months has been recommended for postpartum OVT, while no anticoagulation has been suggested for incidentally detected cancer-associated OVT.
Keywords: anticoagulants; ovary; venous thrombosis